PENGARUH ATRAKSI WISATA TERHADAP KEPUTUSAN BERKUNJUNG DI KAMPUNG BUDAYA BETAWI SETU BABAKAN - Al Fatah, Rayya; Astuti, Anindita Budi; Mufidah, Lina (Jurnal Perhotelan dan Pariwisata, 2023)
Tourist attractions play a crucial role in attracting visitors to a destination. This study investigates the influence of cultural attractions on tourists' decisions to visit Kampung Budaya Betawi Setu Babakan. Using a quantitative method with 382 respondents, data were collected through questionnaires and analyzed with descriptive statistics and the Spearman correlation test. The findings reveal that visitors are highly satisfied with the spatial layout, cleanliness, and cultural presentation at the destination. The most influential factors in decision-making include visual displays and the overall cultural atmosphere. A positive and significant correlation exists between cultural attractions and visit decisions. These results suggest that enhancing the quality and diversity of cultural attractions can effectively increase tourist interest. The study provides valuable insights for destination managers and local authorities in planning sustainable cultural tourism strategies. Keywords: Tourist attractions, visit decision, cultural tourism, Setu Babakan